Fio a fio, ponto a ponto, novos começos e outros finais: a voz e a vez das princesas em Ana Maria Machado - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Considering the relevance of gender discourse, the parodic revisiting and the incentive of reading in the works of the author Ana Maria Machado, the present study had like objective check which resources used for her to elaboration of tightly emancipatory literary productions for children. We select the following works to constitute the corpus of this research: : História meio ao contrário (1978), O príncipe que bocejava (2004), A princesa que escolhia (2006) e Uma, duas, três princesas (2013), since such narratives are configured as modern revisiting of classic fairy tales, performed through the parodic dialogue established with these traditional tales. In the selected tales, we investigate issues related to the representation of female identities in the context of interpersonal relations, verifying that the female characters of the narratives, be they actors or supporting cast, do not subscribe in the perspective of submission that often are found in the classics narratives. In addition, we have lunched the illustrious work of estetic elaboration undertaken by Ana Maria in the production of her tales. The meticulous work with the text demonstrates how skilled she is by associating a language accessible to children with a poetic structure that matches the great classics of world literature.
Keywords: Literatura infantil e juvenil; Ana Maria Machado; Gênero; Paródia; Children's and youth literature; Ana Maria Machado; Gender; Parody; LINGUISTICA, LETRAS E ARTES::LINGUISTICA